2021
DOI: 10.1088/1674-1056/abff22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the potential function and strain rate on mechanical behavior of the single crystal Ni-based alloys: A molecular dynamics study*

Abstract: Molecular dynamics has been widely used to study the fundamental mechanism of Ni-based superalloys. However, the effect of the potential function and strain rate on mechanical behavior has rarely been mentioned in the previous molecular dynamics studies. In the present work, we show that the potential function of molecular dynamics can dramatically influence the simulation results of single crystal Ni-based superalloys. The microstructure and mechanical behavior of single crystal Ni-based superalloys under fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Such a comprehensive comparison can help researchers to deeply understand the advantages and limitations of the model, to obtain more comprehensive and accurate results. Yin et al [99] studied the influence of different potential functions on the simulation results, showed that different potential functions lead to different microstructure characteristics and mechanical properties, and selected the potential function most suitable for mechanical deformation. On this basis, the effect of strain rate on mechanical deformation was studied.…”
Section: Research Status and Application Analysis In Aluminate Slagmentioning
confidence: 99%
“…Such a comprehensive comparison can help researchers to deeply understand the advantages and limitations of the model, to obtain more comprehensive and accurate results. Yin et al [99] studied the influence of different potential functions on the simulation results, showed that different potential functions lead to different microstructure characteristics and mechanical properties, and selected the potential function most suitable for mechanical deformation. On this basis, the effect of strain rate on mechanical deformation was studied.…”
Section: Research Status and Application Analysis In Aluminate Slagmentioning
confidence: 99%